Engineering practices as a framework for STEM education: a proposal based on epistemic nuances - Cristina Simarro; Digna Couso (SpringerOpen, 2021)
Abstract The role of engineering education has gained prominence within the context of STEM education. New educational perspectives such as the National Research Council's Framework for K-12 Science Education consider engineering practices one of the central pillars of a sound STEM education. While this idea of developing a set of practices analogous to those of professional engineering resonates with recent views of STEM education research, current approaches such as the NRC's Framework seem too dependent on and interlinked with the list for scientific practices and adheres to this list too strictly. This paper draws on the NRC's Framework proposing a new set of engineering practices that seek to incorporate the epistemic nuances that differentiate engineering from science. The nine engineering practices proposed contain epistemological nuances that are missing in other proposals, including essential aspects such as problem scoping, identifying multiple solutions, selecting, testing and improving solutions and materializing solutions. This epistemic approach may facilitate students' content learning and thinking development, offering a more comprehensive and realistic view of the STEM fields.